Exploring the information flow and dissemination practices of the internally displaced persons in San Jose Del Monte Heights - Martinez, Jasmine G.
An important aspect of movement of the internally displaced persons are their access to information necessary for them, such as the cause of their displacement, job opportunities, schooling, and health concerns. This access to information is manifested in many ways such as information dissemination of the government agencies, and the information seeking behaviors of the people. These are what the study explored and tried to find out.